Effects of Organic Manures and Green Manuring on Growth, Yield, Economics and Quality of Lemongrass (Cymbopogon Flexuosus L.) In Custard Apple (Annona Squamosa L.) Based Agri-Horti System (Bangladesh Journal of Botany, 2021)
A field experiment was conducted to explore the effects of organic manures and green manuring practices on growth, yield attributes, quality and economics of lemongrass (Cymbopogon flexuosus L.) under custard apple (Annona squamosa L.) based agri-horti system. The findings indicated that growth, yield attributes and yield as well as oil composition, soil nutrient status, microbial populations were significantly increased due to the use of both organic manures and green manuring. The significantly higher results were obtained with vermicompost (2.5 t/ha) + Azotobacter, which was found superior over other practices in terms of growth, yield attributes, oil composition and its quality and soil nutrient status as well as economics of crop cultivation.Bangladesh J. Bot. 50(3): 499-506, 2021 (September)